e-Government: online service delivery evaluation in Pahang / Mas Anom Abdul Rashid and Mohd Noor Azman Othman - Abdul Rashid, Mas Anom; Othman, Mohd Noor Azman (2009)
In order to be a developed country, a country must have a good economic status, i.e. income per capita as well as technology adoption. Thus. the level of e-government implementation is also one indicator that a country is to be a developed country one day. Tun Mahathir in his mission to bring this country to a higher level of global acceptance introduced MSC in 1996 with seven proudly presented flagships. After 13 years, we have seen so much improvement and paradigm shift in running our government's administrative activities. The migration from paper-based service to electronic version is well underway and enormous potential of e-government application being implemented. To look at e-government success, assessments are often conducted at the international and national level. Therefore, on that pretext, the writers feel that there is also a need to look at the local or state level as well because it does contribute to upholding what has been planned at the higher level. This paper assesses the current state of Pahang online service delivery system and the level of acceptance and satisfaction towards the services offered by Pahang state government in meeting the national e-government requirements.